Reaksi Pasar Atas Penerbitan Sukuk (Studi Pada Emiten Saham Penerbit Sukuk Periode 2008-2012) - Vita Fatimatuzzahra; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Issuance of Sukûk’s corporation, it can be an opportunity for many companies to become proponent necessity for funding and business expansion. Sukûk publication announcement is an information for investors in order to assess it based on their investment decisions. In order to get the investment decisions, investors often based on the signals that had been given by the company. That signal can caused the changes of demand and supply’s shares. This study aims to find out the reaction of the stock from the Sukûk publication as indicated by the presence of abnormal returns around the date of publication and the Trading Volume Activity (TVA) difference which is occured before and after Sukûk publication.This study uses event study approach, it carries out on 11 issuer stock of Sukûk publisher which is listing in Indonesia Stock Exchange period : 2008-2012. This study also uses observation period for 81 days, they are t - 10 (70 days before publication), t - 0 (event date) and t +10 (10 days after publication). The hypothesis calibration of this thesis uses a one sample t - test and paired t - test.The results of this study is based on a statistical test with a significance level (α) = 5 %resulted AAR which was in a significantly positive on t - 2 at 0.03711 and significantly negativeat t +9 of 0.03. In contrast with TVA, the statistic results showed probability value of 0.026,which means there is a significant different of trading volume activity before and after ofSukûk publication. The lack of information about Sukûk also caused there is significant AARreaction only in some poriods of observation and significant negative TVA . REFERENCESAccounting and Auditing Organisation for Islamic Financial Institution. 2004. Investment Sukûk. Sharia Standart. Bahrain.Afaf, Nafiah. 2007. Analisis Pengaruh Pengumuman Penerbitan Obligasi Terhadap Return Saham di Bursa Efek Jakarta. Tesis S2 yang tidak dipublikasikan. Bogor Institut Pertanian Bogor.Alwi, Syafaruddin. 1994. Alat-alat Analisis Dalam Pembelanjaan, Edisi Revisi/Keempat, Yogyakarta: Andi Offset.Al-Quran dan Terjemahannya. 2003. Tafsir Fi Zhilalil Qur’an. Jilid 6. Jakarta: ema Insani Press.Ang, Robert. 1997. The Journal of Financial Research. Buku Pintar Pasar Modal Indonesia Vol V : 3. Jakarta: Media Staff Indonesia The Journal of Financial Research. Vol V : 3Anshori, Muslich, Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press.Anwar,Choirul. 2004. Studi Peristiwa Reaksi Pasar terhadap Pemilihan Umum tanggal 5 April 2005 pada Bursa Efek Jakarta. Jurnal Ekonomi & Bisnis No.2 Jilid 9 Badan Pengawas Pasar Modal dan Lembaga Keuangan. 2006. Peraturan No.IX.A.13 tentang Penerbitan Efek Syariah. JakartaBodie, Zvi, Alex Kane, dan Alan J. Marcus. 1999. Investments. Fourth Edition. Boston: McGrae-Hill Inc.Bhattacharya U, H, Doouk & B. Jorgenson,2000, When Evement is Non An Event. The Curious Care of An Emerginal Market, Journal of Financial Economies Vol 55Brigham, Eugene F. Dan Joel F. Houston. 1998. Fundamentals of Financial Management. Eight Edition. Florida: Harcourt Inc.Budiarto, Arif Murtanto. 2002. Event Study: Telaah Metodologi dan Penerapannya di Bidang Ekonomi dan Keuangannya. Jurnal Bisnis dan Akuntansi. Vol 4, No.3: 295-320Bursa Efek Indonesia (BEI). 2004. Studi tentang Investasi Syariah di Pasar Modal Indonesia. (Online) www.idx.co.id, diakses pada 16 Oktober 2013Bursa Efek Indonesia. 2007. Mengenal Pasar Modal. (Online) www.idx.co.id, diakses pada 02 September 2013Cheng, Wei, N. Visaltanachoti, dan P.Kesayan.2005. A stock market reaction following convertible Bond Issuance: evidenve from japan. International Journal of Business, Vol. 10: 323-339Campbell, John Y, Andrew W Lo, dan A. Craig McKinlay. 1996. The Econometrics of Financial Markets. US: Princeton University PressDarsono dan Ratri Dian H.2012. Pengaruh Karakteristik Perusahaan Terhadap Struktur Modal Perusahaan Manufaktur yang Terdaftar Pada Bursa Efek Indonesia. Volume I, No. 1. Diponegoro Journal of Accounting.Dewan Syariah Nasional. 2002. Fatwa No.32/DSN/MUI/IX/2002 tentang Obligasi Syariah. (Online) www.bapepam.go.id diakses pada 01 November 2012Dewan Syariah Nasional. 2002. Fatwa No.33/DSN/MUI/IX/2002 tentang Obligasi Syariah Mudhârabah. (Online) www.bapepam.go.id diakses pada 01 November 2012Dewan Syariah Nasional. 2004. Fatwa No 40/DSN/MUI/X tentang Pasar Modal dan Pedoman Umum Penerapan Prinsip Syariah di Pasar Modal. (Online) diakses pada 1 November 2012.Dewan Syariah Nasional. 2002. Fatwa No.41/DSN/MUI/IX/2002 tentang Obligasi Syariah Ijarah. (Online) www.bapepam.go.id diakses pada 01 November 2012Endri, 2011. Corporate Governance Terhadap Peringkat Sukûk Korporasi di Indonesia. Jurnal Keuangan dan Perbankan. Vol.15, No.2: 178-190Elfakhani, Said, dan M. Kabir Hassan dan Yusuf Sidani, 2005. Comparative Performance of Islamic Versus Secular Mutual Funds. LebanonFatmawati, Sri dan Marwan Asri. 1999. Pengaruh Stock Split terhadap Likuiditas saham yang diukur dengan besarnya Bid-ask spread di Bursa Efek Jakarta. Jurnal Ekonomi dan Bisnis Indonesia. Vol 14: 93-110Foster, G. 1986. Financial Statement Analysis, 2nd edition. Engglewood Cliffs. New Jersey: Prentice Hall InternationalHartono, dan Jogiyanto. 2003. Teori Portfolio dan Analisis Investasi. Yogyakarta: BPFEHusnan, Suad. 1998. Dasar-dasar Teori Portofolio dan Analisis Sekuritas. Yogyakarta: UPP AMP YKPN.International Organization of Securities Commissions. 2004. Islamic Capital Market Fact Finding Report. Report Of The Islamic Capital Market Task Force Of The International Organization Of Securities Commissions. SpanyolJogiyanto. 2000. Teori Portfolio dan Analisis Investasi. Edisi Ketiga, Yogyakarta: Fakultas Ekonomi Universitas Gajah Mada.Jogianto,2008, Teori Portofolio dan Analisis Investasi,Edisi Kelima, BPFE UGM, YogyakartaJones, Charles P. 2002. Investments. Eight Edition. New York: John Wiley & Sons, Inc.Karim, Adiwarman. 2004. Bank Islam: Analisis Fiqih dan Keuangan. Jakarta: Raja Grafindo PersadaKasmir, 1999, Bank dan Lembaga Keuangan Lainnya, Edisi Baru, PT.RajaGrafindo Persada, JakartaLestari, Elly. 2011. Pengujian Reaksi Pasar Terhadap Perusahaan yang Melakukan Stock Splits Berdasarkan Rasio Split di Bursa Efek Indonesia. Tesis. Universitas Airlangga.Mannan, M. Abdul. 2007. Obligasi Syariah. (Online) http://badilag.net diakses 5 Desember 2010Manurung, Adler Haymans & Ira, Cahyanti. 2002. Pengaruh Peristiwa Politik (Pengumuman Hasil Pemilu Legislatif, Pengumuman Susunan Kabinet, Reshulffle Kabinet) terhadap Sektor-sektor Industri di Bursa Efek Jakarta.Meidawati, Neni dan Mahendra Harimawan. 2004. The Impact of Bank Restructuring Announcements on The Banking Stock Prices: The Cases of Indonesia’s Bonds on May 28, 1999. Gajah Mada International Journal of Business. No I : 119-139Mujahid, dan Tettet Fitrijanti. 2010. Pengaruh Penerbitan Obligasi Syariah (Sukûk) Perusahaan Terhadap Reaksi Pasar. SNA XIII. Universitas Jenderal Soedirman Purwokerto.Nasution, Mustafa Edwin & Huda, Nurul. 2008. Investasi pada pasar Modal Syariah. Jakarta: KencanaNursiam dan Puteranto, Lastiyono Doso. 2004. Analisis Efisiensi PasarModal Indonesia Periode 1998-2000 (Studi pada PT.Bursa Efek Jakarta). Jurnal Akuntansi dan Keuangan.Nusantara, Agung. 2004. Pasar Modal Islami Antrara Harapan dan Kenyataan. Fokus Ekononi. Agustus, Vol. 3, No. 2Pratiwi, Widiati. 2012. Pengaruh Informasi Penerapan Good Corporate Governance Terhadap Kenaikan Harga Saham Pada PT Adhi Karya (Persero) Tbk. Skripsi. Universitas Pendidikan Indonesia.Ryandono, Muhamad Nafik H. 2009. Bursa Efek dan Investasi Syariah. Jakarta: Serambi.Siamat, Dahlan. 2005. Manajemen Lembaga Keuangan. Edisi Kelima. Lembaga Penerbit Fakultas Ekonomi Universitas Indonesia.Sudana, I Made. 2009. Manajemen Keuangan Teori dan Praktik. Surabaya: Airlangga University Press.Sudarsono, Heri. 2008. Bank dan Lembaga Keuangan Syariah. Yogyakarta: EkonisiaSugiyono. 2009. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung:AlfabetaSukmaningrum, Puji Sucia. 2012. Reaksi Pasar Terhadap Pengumuman Penerbitan Obligasi Syariah di Bursa Efek Indonesia. Program Sarjana Universitas AirlanggaSupranto J. 2009. Statistik Teori dan Aplikasi. Edisi Ketujuh. Jakarta: Erlangga.Suryabrata, Sumadi. 2009. Metodologi Penelitian. Jakarta: Raja Grafindo Persada.Suryomurti, Wiku. 2011. Supercerdas Investasi Syariah, Jakarta: Qultum MediaSutedi, Adrian. 2011. Pasar Modal Syariah. Jakarta: Sinar GrafikaTandelilin, Eduardus. 2001. Analisis Investasi Dan Manajemen Portofolio. Yogyakarta: BPFE YogyakartaTariq, Ali Arsalan. 2004. Managing Financial Risk of Sukûk Structures. Disertasi, tidak diterbitkan. UK. Longboroungh University.Touriq, Muhammad. 2011. Arah Kebijakan Pengembangan Pasar Modal Syariah. Iqtishodia Jurnal Ekonomi Islam Republika. Hal.23 Tahun 2011Wahid, Nazaruddin Abdul. 2010. Sukûk: Memahami dan Membedah Obligasi pada Perbankan Syariah. Yogyakarta: Ar-Ruzz Media.www.adiwarmankarim.comwww.duniainvestasi.comwww.finance.yahoo.comwww.idx.co.idwww.standartandpoors.com